ENT300 (Fundamental of Entrepreneurship) : Ultra Laundry / Terrance Manja Anak Janting...[et al.] - Janting, Terrance Manja; Louis, Josephson; Sitin, Alsee Grace; Hisham, Nurul Arfiqqah; Kamal, Vanessa Anie; Japong, Cinderell Francis (2015)
The name of our company is Ultra Laundry. The business is in the form of partnership which consists of six members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is laundry service. There are no sleeping partners and all are entitled to participate in the business management. We had agreed that Terrance Manja Anak Janting as our General Manager, Nurul Arfiqqah binti Hisham as the Administration Manager, Alsee Grace Anak Sitin and Josephson Louis Anak Nako as the Operation Manager, Vanessa Anie Anak Kamal as the Financial Manager and Cinderella Francis Japong as the Marketing Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability of the partner. The management team will be led by the General Manager and assist by the other managers. The General Manager is responsible in planning, leading, controlling and organizing the business. The Administration Manager is responsible for the job that related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operation Manager is responsible to the entire job that related to the operation and will be supervise and coordinate the operation of the busines3R Y The Marketing Manager will be responsible to create the marketing plan, identifying the customer's need and demand, identifying the competitors, target market, market size and forecast the future market. Lastly, the Financial Manager will be handled the financial matters such as preparing the budget and financial statement for expenses of each departments and controlling the flow of the money of the organization